Hydration status and liver function of young men before and after Ramadan fasting - Ibrahim, Nur Susan Iriyanti; Hardinsyah, Hardinsyah; Setiawan, Budi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2018)
The objective of this study was to identify and analyse the hydration status and liver function of young men before and during Ramadan fasting (RF). The study design was a prospective cohort into 1st period (one week before fasting) and 2nd period (the last ten days of fasting). The subjects were 18 healthy young men (19-30 years old). Data on dietary intake were collected using food record 3x24h, body composition were collected using bioelectrical impedance analyser (BIA), hydration status and liver function data were measured trough urine and blood sample. This study showed significant differences in body weight, fat body mass, body mass index (BMI), body water, intake of energy, protein, fat, carbohydrate, and water, hydration status (serum osmolality and urine density), and liver function (SGOT and SGPT levels) before and during RF (p<0.05). There were significant correlation between fasting status and SGPT levels (p<0.05). The study concluded that Ramadhan fasting has a positive effect to control body weight and improve liver function measured by SGOT and SGPT levels.